EVALUASI PELAPORAN DAN PERTANGGUNGJAWABAN DANA DESA (STUDI PADA DESA RINGINHARJO KABUPATEN BANTUL) - Umbing, Golda Belladonna; Halim, Abdul (ABDI EQUATOR, 2021)
This research aims to evaluate the reporting and accountability of village funds and to identify issues occurring during the reporting and accountability processes of village funds at Ringinharjo Village. This research is qualitative research applying the case study method. Compatibility between the reporting and accountability of village funds was evaluated by employing the percentage descriptive analysis method. The issues identified were investigated by interviewing the village officials, officials of governance division ofthe subdistrict, officials of village government division of the regency, and auditing inspectorates. Research results display a compatibility between the reporting and accountability with the percentage of 52.63% indicating that the arrangement of both reporting and accountability is categorized as less compatible with the applicable regulations. Problems existing in the reporting and accountability of village funds at Ringinharjo Village were caused by the number and capabilities of human resources of the activity management team the Village Management Team (TPK, Tim Pengelola Kegiatan); the short period between disbursement and reporting activities; the changing regulations, no standards in reporting, and minimum monitoring from both the inspectorate and regency due to many objects to monitor and limited amount of monitoring team.